Sleep disturbances in allergic rhinitis: disease and/or the drug? - Patil, Anant D. (International Journal of Basic & Clinical Pharmacology, 2017)
Allergic rhinitis is a common chronic disease in adults as well as children. Allergic rhinitis has negative impact on sleep and quality of life of the patient. Antihistamines are widely used in the management of allergic rhinitis. First generation antihistamines cause sedation and drowsiness. Second generation antihistamines cause minimal or no sedation. There is difference in propensity to cause sedation amongst second generation antihistamines. As sleep is important for physical as well as mental health, present article reviews impact of allergic rhinitis and antihistamines on sleep.